Pengaruh Program Latihan Fisik Terstruktur, Nutrisi, Dan Strategi Pembelajaran Aktif Terhadap Kebugaran Jasmani Dan Prestasi Atlet Muda Di Sekolah Menengah - Hulu, Agil Hagaini (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the effect of structured physical training programs, nutrition, and active learning strategies on physical fitness and athletic performance of young athletes in secondary schools. A quasi-experimental design was employed with a sample of 60 students divided into experimental and control groups. Research instruments included physical fitness tests (muscle strength, cardiovascular endurance, speed, and flexibility) and athletic performance assessments. The intervention was conducted over 12 weeks with structured training, nutrition education, and active learning strategies. The results indicated significant improvements in physical fitness and athletic performance in the experimental group compared to the control group. These findings confirm that integrating physical training, nutrition, and active learning strategies has a synergistic effect on the development of young athletes. Implementing an integrated program in secondary schools can enhance physical performance, athletic achievement, as well as student motivation and discipline.